PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI PEMODERASI - Putra, Bayu Darma; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2015)
There are many studies about the effect of corporate social responsibility on firm value, however they show inconsistent results. Nugraheni (2010)  found the corporate social responsibility has significant effect on  firm value, on the Agustine (2013) found different result. This suggests there are other factors that affect the relationship between  corporate social responsibility on firm value. This study used profitability as a moderating variable. This study aimed to determine the effect of corporate social responsibility to the firm value with profitability as moderating variables in mining companies in Indonesia Stock Exchange 2011-2013. The total sample of 26 industries mining the probability sampling method. Data collected by non-behavioral observation techniques. The analysis technique used is a simple linear regression analysis and regression analysis moderation. The results showed that (1) corporate social responsibility positive effect on firm value, (2) the profitability able to strengthen the influence  of corporate social responsibility on firm value.
Keywords: profitability, firm value, corporate social responsibility, mining industry